Perspective—Conducting Polymer Hybrids as Diagnostic Chemosensors. Issue 3 (1st March 2022) - Haynes, A.; Gouma, P. I.
Abstract : Polyaniline is a conducting polymer in which both redox and protonating/ deprotonating conduction mechanisms are activated in the presence of gaseous compounds, making it a gas sensor. Resistive chemosensors based on PANI, in particular, have been well studied for their gas sensing properties and are considered important sensing materials for a wide range of applications as they operate at room temperature. There is, however, a novel class of polyaniline hybrids with cellulose acetate that may be suitable for detecting biomarkers emitted from the skin and in measuring the pH of breath condensate for diseases and thus, worth studying them further.